Associations of mitochondrial DNA 3777-4679 region mutations with maternally inherited essential hypertensive subjects in China - Ye Zhu; Jia You; Chao Xu; Xiang Gu (BMC, 2020)
Abstract Background Nuclear genome or family mitochondrial screening system has become the hot focus of studies into essential hypertension. The role of mitochondrial DNA (mtDNA) in sporadic Chinese patients with hypertension has not been fully understood. The study was to evaluate the associations of mtDNA mutations with maternally inherited essential hypertensive subjects in China. Methods From June 2009 to June 2016, a total of 800 gender-matched Chinese patients with maternally inherited essential hypertension (MIEH) and control group were 1:1 enrolled in this case-control study. Genomic DNA was extracted from each person's peripheral blood cells. The main mtDNA locations for MIEH were screened with oligodeoxynucleotides 3777-4679 bp, analyzed and compared with the updated consensus Cambridge Sequence. Pathogenic mtDNA mutations were identified from the mitochondrial map. Results MIEH subjects presented significantly higher values than those of control group in abdominal circumference (AC), waist circumference (WC), body mass index (BMI), fasting blood glucose (FBG), triglyceride (TG), low-density lipoprotein cholesterol (LDL) and renal function (P < 0.05). MIEH subjects carried more amino acid changes and coding sequence variants (P < 0.01) than control group. The allele frequencies of the eight single nucleotide polymorphisms (SNPs) were significantly different between the two groups, including m.3970 C > T, m.4048G > A, m.4071C > T, m.4086C > T, m. 4164A > G and m.4248 T > C in ND1 gene, and m.4386 T > C and m.4394C > T in tRNAGln gene(P < 0.001). Fifty-five homoplasmic or heteroplasmic mutations were detected in 5 genes: ND1, tRNAIle, tRNAMet, tRNAGln and ND2 gene. The ND1 gene was the main mutation site, where the most mtDNA mutation was m.3970 C > T. Conclusions The mtDNA mutations were involved in the process of MIEH. We identified mitochondrial genetic characteristics in MIEH patients in China. The present research serves as a solid foundation for further detailed research on the association between MIEH and mitochondrial dysfunction, and their causal relationship in Chinese and other populations with a similar lifestyle.